2022
DOI: 10.1186/s11658-021-00301-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of polyphenols in overcoming cancer drug resistance: a comprehensive review

Abstract: Chemotherapeutic drugs are used to treat advanced stages of cancer or following surgery. However, cancers often develop resistance against drugs, leading to failure of treatment and recurrence of the disease. Polyphenols are a family of organic compounds with more than 10,000 members which have a three-membered flavan ring system in common. These natural compounds are known for their beneficial properties, such as free radical scavenging, decreasing oxidative stress, and modulating inflammation. Herein, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 225 publications
(266 reference statements)
1
52
0
Order By: Relevance
“…Most plant derived polyphenols possess both antioxidant as well as prooxidant properties ( George et al, 2011 ; Asuzu et al, 2019 ; Jomová et al, 2019 ; Maleki Dana et al, 2022 ). Several studies have shown that in the presence of copper ions polyphenolic compounds can act as pro oxidants leading to cellular breakage of DNA via ROS formation ( Said Ahmad et al, 1992 ; Ahsan and Hadi, 1998 ; Khan and Hadi, 1998 ; Ahmad et al, 2000 ; Azam et al, 2004 ; Ahmad et al, 2005 ; Farhan et al, 2015a ; Arif et al, 2015 ).…”
Section: Role Of Reactive Oxygen Species In Cancer Cell Deathmentioning
confidence: 99%
“…Most plant derived polyphenols possess both antioxidant as well as prooxidant properties ( George et al, 2011 ; Asuzu et al, 2019 ; Jomová et al, 2019 ; Maleki Dana et al, 2022 ). Several studies have shown that in the presence of copper ions polyphenolic compounds can act as pro oxidants leading to cellular breakage of DNA via ROS formation ( Said Ahmad et al, 1992 ; Ahsan and Hadi, 1998 ; Khan and Hadi, 1998 ; Ahmad et al, 2000 ; Azam et al, 2004 ; Ahmad et al, 2005 ; Farhan et al, 2015a ; Arif et al, 2015 ).…”
Section: Role Of Reactive Oxygen Species In Cancer Cell Deathmentioning
confidence: 99%
“…At present, chemotherapy remains the main treatment for tumors [ 35 ]. Mutations of the targets of chemotherapeutic drugs, or modifications of the signaling pathway components involved, can reduce drug efficacy so that the tumor develops resistance to the chemotherapeutic drugs [ 36 ]. The mechanisms of tumor resistance to chemotherapeutic drugs are still very complex [ 37 ].…”
Section: The Signaling Pathways In Tumor Drug Resistancementioning
confidence: 99%
“…Due to ineffective therapy, there is an urgent need to develop a novel regimen that would be able to overcome such obstacles as GB tumor heterogeneity or drug resistance. One of the therapeutical strategies that are being taken into consideration is a combined treatment targeting multiple pathways crucial for neoplastic cell survival [ 18 , 19 ]. This is the basis of the process called chemosensitization, which assumes the use of a non-toxic compound that is able to enhance the activity of a chemotherapeutic [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A combined therapy involving a chemical that targets one of the mechanisms of chemoresistance, including drug uptake, its metabolism, or cell death and survival, is expected to improve pharmacotherapy efficacy. The compounds that possess such properties are polyphenols [ 19 ].…”
Section: Introductionmentioning
confidence: 99%